2012
DOI: 10.1371/journal.pntd.0001885
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Procedure for Precise Quantification of Schistosoma japonicum Eggs in Bovine Feces

Abstract: Schistosomiasis japonica is a zoonosis with a number of mammalian species acting as reservoir hosts, including water buffaloes which can contribute up to 75% to human transmission in the People's Republic of China. Determining prevalence and intensity of Schistosoma japonicum in mammalian hosts is important for calculating transmission rates and determining environmental contamination. A new procedure, the formalin–ethyl acetate sedimentation-digestion (FEA–SD) technique, for increased visualization of S. japo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 34 publications
1
42
0
Order By: Relevance
“…Twenty samples were randomly selected for further microscopic examination using a modification of the FEA-SD technique [ 26 , 29 ]. After processing using this procedure, S. japonicum eggs were found in 16 samples by microscopy ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty samples were randomly selected for further microscopic examination using a modification of the FEA-SD technique [ 26 , 29 ]. After processing using this procedure, S. japonicum eggs were found in 16 samples by microscopy ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Validation of the qPCR by microscopy . A random selection of 20 human stool samples that were: qPCR-positive and KK-negative; qPCR- and KK-positive; or qPCR- and KK-negative were re-examined by microscopy after processing, using a modification of the formalin-ethyl acetate sedimentation-digestion (FEA-SD) technique developed recently for the precise quantification of S. japonicum eggs in bovine stool [ 26 , 29 ]. The remaining volume of stool not used for DNA extraction was used for the microscopic examination.…”
Section: Methodsmentioning
confidence: 99%
“…The sensitivity of the test can be improved by using multiple stool samples over several consecutive days, but this can compromise its simplicity and cost-effectiveness, and this modified approach can suffer from low compliance due to the reluctance of individuals to provide more than one stool sample for examination (57). While modifications to the KK test to improve the test efficacy have been suggested (65,66), the inherent drawbacks have yet to be resolved.…”
Section: Direct Parasitological Diagnosismentioning
confidence: 99%
“…A study by Wu et al in Leyte, using a polymerase chain reaction (PCR)-based diagnostic method, showed the S. japonicum prevalence in carabao was 52% [13]. Another recent study of bovines in Samar province in 2010 using real time quantitative PCR (qPCR) showed similar results with greater than 90% of bovines being infected with S. japonicum [14,15]. Thus, there is a little question that bovines play a major role in the transmission of S. japonicum in the Philippines and should thus be targeted for the treatment and vaccination.…”
Section: Integrated Control – the Way Forwardmentioning
confidence: 99%